Analysis of the Determinants of International Trade of Countries in The Asia-Pacific Economic Region (APEC) - Asnafi, Muhamad Faiz; Choiri, Miftakhul (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2024)
International trade is the engine of growth for a country to increase its economic size. This study explores the determinants of trade flows between Asia-Pacific Economic Cooperation (APEC) member economies in the initial period of APEC formation in 1989 to 2020 using Newton's Universal Gravity theory approach. This study uses quantitative analysis method with the estimation technique used is Poisson Pseudo-Maximum Likelihood (PPML). This study uses ten independent variables: GDP of the home country and trading partner, geographical distance, population of the home country and trading partner, and several dummy variables including: common language, contiguous border, common colonial history, membership in the World Trade Organization (WTO), and regional trade agreement (RTA). The results show that trade flows between APEC economies are significantly influenced by GDP of home and trading partner countries, geographical distance, population of home and trading partner countries, and several dummy variables, including common language, contiguous borders, common colonial history, and membership in the WTO. Meanwhile, the Regional Trade Agreement (RTA) variable has no significant effect.